Effectiveness of acupuncture combined with rehabilitation training vs. rehabilitation training alone for post-stroke shoulder pain: A systematic review and meta-analysis of randomized controlled trials - Zhan, Jie; Wei, Xiaojing; Tao, Chenyang; Yan, Xiaoting; Zhang, Peiming; Chen, Rouhao; Dong, Yu; Chen, Hongxia; Liu, Jianhua; Lu, Liming (Frontiers in Medicine, 2022)
Background: Post-stroke shoulder pain (PSSP) is characterized by shoulder pain on the hemiplegic side, which can limit stroke patients' physical activity. Acupuncture combined with rehabilitation training (AR) has been widely used in PSSP, but the evidence of its effectiveness is still unclear. Objective: To evaluate the effect and safety of AR versus rehabilitation training (RT) alone on PSSP. Methods: Six databases were systematically searched from inception to February 2022. Only randomized controlled trials (RCTs) comparing the effect of AR with RT alone on PSSP were considered. Primary outcome was shoulder pain. Secondary outcomes included upper limb motor function, activities of daily living (ADL), shoulder range of motion (ROM), and adverse events (AEs). Subgroup analysis and sensitivity analysis were also conducted. Quality assessment was implemented based on Cochrane risk of bias (ROB) criteria which consists of seven items. When more than four items in a study were judged as low ROB, the overall quality of this study was considered as low risk. Results: Forty studies were included in qualitative analysis, and 35 (87.5%) studies with 2554 patients were included in meta-analysis. Fourteen (35.0%) of the 40 studies were of moderate to high quality. The meta-analysis results showed that AR is better than RT alone in reducing shoulder pain (MD -1.32, 95% CI -1.58 to -1.07), improving upper limb motor function (MD 6.81, 95% CI 4.95 to 8.67), ADL (MD 11.17, 95% CI 9.44 to 12.91), and shoulder ROM (internal rotation: MD 10.48, 95% CI 8.14 to 12.83; backward extension: MD 7.82, 95% CI 6.00 to 9.64; anteflexion: MD 12.88, 95% CI 5.47 to 20.29; external rotation: MD 11.40, 95% CI 6.17 to 16.64; abduction: MD 16.96, 95% CI 8.61 to 25.31) without obvious AEs. Conclusion: AR may be better than RT alone for the improvement of shoulder pain, upper limb motor function, ADL, and shoulder ROM, without obvious AEs in PSSP patients. However, considering the clinical and statistical heterogeneity, our findings need to be interpreted with caution. More rigorous RCTs of this area should be conducted in the future.